Relationship of Scabies With Pioderma: As a Risk Factor - Yahya, Yulia Farida; Argentina, Fifa; Rusmawardiana, Rusmawardiana (Sriwijaya Journal of Medicine, 2018)
Scabies is a parasitic infestation of the skin, that is affecting on the low income and crowded community in many tropical countries, especially developing countries such as Indonesia. Scabies infestation increases the incidence of secondary pyoderma include impetigo, folliculitis, cellulitis, ecthyma, abscess. Secondary pyoderma is a skin infection disease mainly caused by group A Streptococcus (GAS) and Staphylococcus aureus (SA). Pyoderma is a risk factor for the glomerulonephritis infection, rheumatic diseases, which significantly increases morbidity and mortality, causing the government burden. The aim of this study is determining the etiology and correlation of pyoderma infection in scabies patient. To determine sosio-demographic included sex, age in pediatric patients in primary schools (SD) in the district of Kertapati Palembang. The study design was cross sectional, and study samples were new scabies patients in the elementary school (age 6-14-year-old) with or without pyoderma. Clinical findings included history, physical examination and diagnostic procedure, which was investigation of skin scraping specimen material (SSB = skin surface biopsy) in confirmation with dermoscopic polar examination (DS) to show Sarcoptes scabiei mites. Microbiological examination with Gram stain identified the etiology of pyoderma. Results of this study shows that there was a significance relationship between scabies infestation and pyoderma in children in elementary school. Staphylococcus aureus dan GAS are the most common caused of pyoderma in pediatric patients with scabies. Conclusion is there is a significant correlation between scabies and pyoderma. There is a need to provide scabies and pyoderma medication at primary care health center as well as counseling for prevention in Palembang area with crowded population periodically.